Pengembangan Aplikasi Administrasi Digital Pengendalian Stok Barang pada PT X - Marcellia Fauzia; Roni Faslah; Rayi Dwipanilih (Indo Publishing, 2026)
This study aims to develop a digital administrative application for inventory control at PT X to enhance the effectiveness and efficiency of stock management. The identified problems indicate that the processes of recording, monitoring, and reporting stock are still conducted manually, which may lead to delays in information, recording errors, and difficulties in real-time stock monitoring. The research method employed is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data were obtained through observation, interviews, documentation, and literature review. The application was developed using the AppSheet platform with Google Sheets as the database. The main features developed include stock data management, recording of incoming and outgoing goods, automatic and real-time stock updates, stock reports, and minimum stock notifications. This study is expected to produce a digital administrative application that can support the processes of recording, monitoring, and reporting stock more effectively, accurately, and in an integrated manner. Furthermore, the developed application is anticipated to achieve a high level of feasibility based on assessments from material and media experts, as well as to receive positive responses from users, thereby supporting the stock control process at PT X optimally.